Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

The interplay of local adaptation and gene flow may lead to the formation of supergenes - Paul Jay; Thomas G. Aubier; Mathieu Joron (Molecular Ecology, 2024)
Supergenes are genetic architectures resulting in the segregation of alternative combinations of alleles underlying complex phenotypes. The co‐segregation of alleles at linked loci is often facilitated by polymorphic chromosomal rearrangements suppressing recombination locally. Supergenes are involved in many complex polymorphisms, including sexual, colour or behavioural polymorphisms in numerous plants, fungi, mammals, fish, and insects. Despite a long history of empirical and theoretical research, the formation of supergenes remains poorly understood. Here, using a two‐island population genetic model, we explore how gene flow and the evolution of overdominant chromosomal inversions may jointly lead to the formation of supergenes. We show that the evolution of inversions in differentiated populations, both under disruptive selection, leads to an increase in frequency of poorly adapted, immigrant haplotypes. Indeed, rare allelic combinations, such as immigrant haplotypes, are more frequently reshuffled by recombination than common allelic combinations, and therefore benefit from the recombination suppression generated by inversions. When an inversion capturing a locally adapted haplotype spreads but is associated with a fitness cost hampering its fixation (e.g. a recessive mutation load), the maintenance of a non‐inverted haplotype in the population is enhanced; under certain conditions, the immigrant haplotype persists alongside the inverted local haplotype, while the standard local haplotype disappears. This establishes a stable, local polymorphism with two non‐recombining haplotypes encoding alternative adaptive strategies, that is, a supergene. These results bring new light to the importance of local adaptation, overdominance, and gene flow in the formation of supergenes and inversion polymorphisms in general.

Inversion breakpoints and the evolution of supergenes - Romain Villoutreix; Diego Ayala; Mathieu Joron; Zachariah Gompert; Jeffrey L. Feder; Patrik Nosil (Molecular Ecology, 2021)
The coexistence of discrete morphs that differ in multiple traits is common within natural populations of many taxa. Such morphs are often associated with chromosomal inversions, presumably because the recombination suppressing effects of inversions help maintain alternate adaptive combinations of alleles across the multiple loci affecting these traits. However, inversions can also harbour selected mutations at their breakpoints, leading to their rise in frequency in addition to (or independent from) their role in recombination suppression. In this review, we first describe the different ways that breakpoints can create mutations. We then critically examine the evidence for the breakpoint‐mutation and recombination suppression hypotheses for explaining the existence of discrete morphs associated with chromosomal inversions. We find that the evidence that inversions are favoured due to recombination suppression is often indirect. The evidence that breakpoints harbour mutations that are adaptive is also largely indirect, with the characterization of inversion breakpoints at the sequence level being incomplete in most systems. Direct tests of the role of suppressed recombination and breakpoint mutations in inversion evolution are thus needed. Finally, we emphasize how the two hypotheses of recombination suppression and breakpoint mutation can act in conjunction, with implications for understanding the emergence of supergenes and their evolutionary dynamics. We conclude by discussing how breakpoint characterization could improve our understanding of complex, discrete phenotypic forms in nature.

Genetic architecture and balancing selection: the life and death of differentiated variants - Violaine Llaurens; Annabel Whibley; Mathieu Joron (Molecular Ecology, 2017)
Balancing selection describes any form of natural selection, which results in the persistence of multiple variants of a trait at intermediate frequencies within populations. By offering up a snapshot of multiple co‐occurring functional variants and their interactions, systems under balancing selection can reveal the evolutionary mechanisms favouring the emergence and persistence of adaptive variation in natural populations. We here focus on the mechanisms by which several functional variants for a given trait can arise, a process typically requiring multiple epistatic mutations. We highlight how balancing selection can favour specific features in the genetic architecture and review the evolutionary and molecular mechanisms shaping this architecture. First, balancing selection affects the number of loci underlying differentiated traits and their respective effects. Control by one or few loci favours the persistence of differentiated functional variants by limiting intergenic recombination, or its impact, and may sometimes lead to the evolution of supergenes. Chromosomal rearrangements, particularly inversions, preventing adaptive combinations from being dissociated are increasingly being noted as features of such systems. Similarly, due to the frequency of heterozygotes maintained by balancing selection, dominance may be a key property of adaptive variants. High heterozygosity and limited recombination also influence associated genetic load, as linked recessive deleterious mutations may be sheltered. The capture of deleterious elements in a locus under balancing selection may reinforce polymorphism by further promoting heterozygotes. Finally, according to recent genomewide scans, balanced polymorphism might be more pervasive than generally thought. We stress the need for both functional and ecological studies to characterize the evolutionary mechanisms operating in these systems.

Into the Andes: multiple independent colonizations drive montane diversity in the Neotropical clearwing butterflies Godyridina - Nicolas Chazot; Keith R. Willmott; Fabien L. Condamine; Donna Lisa De‐Silva; André V. L. Freitas; Gerardo Lamas; Hélène Morlon; Carlos E. Giraldo; Chris D. Jiggins; Mathieu Joron; James Mallet; Sandra Uribe; et al. (Molecular Ecology, 2016)
Understanding why species richness peaks along the Andes is a fundamental question in the study of Neotropical biodiversity. Several biogeographic and diversification scenarios have been proposed in the literature, but there is confusion about the processes underlying each scenario, and assessing their relative contribution is not straightforward. Here, we propose to refine these scenarios into a framework which evaluates four evolutionary mechanisms: higher speciation rate in the Andes, lower extinction rates in the Andes, older colonization times and higher colonization rates of the Andes from adjacent areas. We apply this framework to a species‐rich subtribe of Neotropical butterflies whose diversity peaks in the Andes, the Godyridina (Nymphalidae: Ithomiini). We generated a time‐calibrated phylogeny of the Godyridina and fitted time‐dependent diversification models. Using trait‐dependent diversification models and ancestral state reconstruction methods we then compared different biogeographic scenarios. We found strong evidence that the rates of colonization into the Andes were higher than the other way round. Those colonizations and the subsequent local diversification at equal rates in the Andes and in non‐Andean regions mechanically increased the species richness of Andean regions compared to that of non‐Andean regions (‘species‐attractor’ hypothesis). We also found support for increasing speciation rates associated with Andean lineages. Our work highlights the importance of the Andean slopes in repeatedly attracting non‐Andean lineages, most likely as a result of the diversity of habitats and/or host plants. Applying this analytical framework to other clades will bring important insights into the evolutionary mechanisms underlying the most species‐rich biodiversity hotspot on the planet.

Characterization of a hotspot for mimicry: assembly of a butterfly wing transcriptome to genomic sequence at the HmYb/Sb locus - LAURA FERGUSON; SIU FAI LEE; NICOLA CHAMBERLAIN; NICOLA NADEAU; MATHIEU JORON; SIMON BAXTER; PAUL WILKINSON; ALEXIE PAPANICOLAOU; SUJAI KUMAR; THUAN‐JIN KEE; RICHARD CLARK; CLAIRE DAVIDSON; et al. (Molecular Ecology, 2010)
The mimetic wing patterns of Heliconius butterflies are an excellent example of both adaptive radiation and convergent evolution. Alleles at the HmYb and HmSb loci control the presence/absence of hindwing bar and hindwing margin phenotypes respectively between divergent races of Heliconius melpomene , and also between sister species. Here, we used fine‐scale linkage mapping to identify and sequence a BAC tilepath across the HmYb/Sb loci. We also generated transcriptome sequence data for two wing pattern forms of H. melpomene that differed in HmYb/Sb alleles using 454 sequencing technology. Custom scripts were used to process the sequence traces and generate transcriptome assemblies. Genomic sequence for the HmYb/Sb candidate region was annotated both using the MAKER pipeline and manually using transcriptome sequence reads. In total, 28 genes were identified in the HmYb/Sb candidate region, six of which have alternative splice forms. None of these are orthologues of genes previously identified as being expressed in butterfly wing pattern development, implying previously undescribed molecular mechanisms of pattern determination on Heliconius wings. The use of next‐generation sequencing has therefore facilitated DNA annotation of a poorly characterized genome, and generated hypotheses regarding the identity of wing pattern at the HmYb/Sb loci.

Genomic tools and cDNA derived markers for butterflies - ALEXIE PAPANICOLAOU; MATHIEU JORON; W. OWEN MCMILLAN; MARK L. BLAXTER; CHRIS D. JIGGINS (Molecular Ecology, 2005)
The Lepidoptera have long been used as examples in the study of evolution, but some questions remain difficult to resolve due to a lack of molecular genetic data. However, as technology improves, genomic tools are becoming increasingly available to tackle unanswered evolutionary questions. Here we have used expressed sequence tags (ESTs) to develop genetic markers for two Müllerian mimic species, Heliconius melpomene and Heliconius erato . In total 1363 ESTs were generated, representing 330 gene objects in H. melpomene and 431 in H. erato . User‐friendly bioinformatic tools were used to construct a nonredundant database of these putative genes (available at http://www.heliconius.org ), and annotate them with blast similarity searches, InterPro matches and Gene Ontology terms. This database will be continually updated with EST sequences for the Papilionideae as they become publicly available, providing a tool for gene finding in the butterflies. Alignments of the Heliconius sequences with putative homologues derived from Bombyx mori or other public data sets were used to identify conserved PCR priming sites, and develop 55 markers that can be amplified from genomic DNA in both H. erato and H. melpomene . These markers will be used for comparative linkage mapping in Heliconius and will have applications in other phylogenetic and genomic studies in the Lepidoptera.

Variable Selection and the Coexistence of Multiple mimetic forms of the Butterfly Heliconius numata - Mathieu Joron; Ian R. Wynne; Gerardo Lamas; James Mallet (Evolutionary Ecology, 1999)